Rubble Stone Masonry Buildings With Cement Mortar: Design Specifications in Seismic and Masonry Codes Worldwide - Schildkamp, Martijn; Silvestri, Stefano; Araki, Yoshikazu (Frontiers in Built Environment, 2020)
Nearly 325 seismic and masonry codes from all over the world have been analyzed, of countries where stone masonry was, or still is, abundantly practiced. This paper compares and summarizes design specifications and construction requirements, with a specific focus on “nominally reinforced rubble stone masonry (NRM) with cement mortar and wooden diaphragms in seismic areas”. Currently, the technique is only allowed and described in some detail in the codes of Nepal, India, China, Tajikistan, Georgia, Iran and Croatia. It is concluded that the design specifications vary greatly without any consensus on the main sizes, dimensions or details. This raises questions about the completeness and correctness, as well as the reliability and actual value of the knowledge in this field. It is further observed that types of stone masonry and stone properties are seldom clearly described in the codes. It is also noted that several countries where stone masonry is still broadly practiced, are currently not allowing the technique (or have no codes in place), such as Afghanistan, Pakistan, Bhutan, Azerbaijan, Kyrgyzstan, Morocco, Tunisia, Turkey, Yemen and Albania. This, however, does not serve the current engineering practices and construction needs in these countries. To address all shortcomings, the paper recommends clear descriptions and terminology; the international adaption of NRM as a fourth masonry category; and the development of a stand-alone code specifically for this technique. Therefore, the authors propose a full assessment, validation, optimization and complementation of the existing knowledge, by means of the current state-of-the-art for calculating, testing and modeling. This envisions a structured research approach with focus on vernacular and traditional construction techniques, called “Non-Engineered 2.0”, for which a research initiative is started under the name “SMARTnet”, meaning “Seismic Methodologies for Applied Research and Testing of non-engineered techniques”. The findings of this paper will serve as the starting point for the upcoming follow-up paper, which will complement the seismic demand with hand-made base shear calculations for countries that still allow the technique. The paper ends with an appeal to experts, academics and final-year students worldwide, to exchange their knowledge and to support the project with their time and expertise.